Assessing potential brief screening questions for use within different social care‐related contexts to identify individuals experiencing gambling‐related harms: A scoping review. (4th September 2022) - Forward, Cat; Norrie, Caroline; Bramley, Stephanie; Wardle, Heather; Stewart, Glenn; Dowridge, Wesley; Nyandu, Steven; Parker, Jaana; Shearer, James; Finch, Emily; Manthorpe, Jill
Abstract: Gambling‐related harms are increasingly recognised as public health concerns internationally. One response is to improve identification of and support for those affected by gambling‐related harms, including individuals who gamble and those close to them, 'affected others'. Adult social care services have been identified as a setting in which screening for gambling‐related harms is suitable and desirable. To achieve this, a tool is required which can identify gambling‐related harms experienced by individuals and affected others. This scoping review aimed to identify whether any brief (i.e. three questions or less) screening tools are being used and, if so, how brief screening for gambling‐related harm is being implemented in health and social care‐related contexts. An international English language scoping review of research and grey literature was undertaken between April and July 2021. The search included single‐item and brief screening tools which have been developed to identify gambling‐related harms for individuals and affected others across a range of health and social care‐related contexts. Findings show that screening tools for gambling‐related harms have been developed for use in health settings rather than in social care contexts. For example within gambling, mental health or substance misuse support services. We found no evidence of a brief or single‐item screening tool for identifying harms to individuals and affected others which is of adequate quality to strongly recommend for use in an adult social care setting. Development of a validated brief or single‐item screening tool is recommended to assist adult social care practitioners to effectively screen, identify, support and signpost people affected by gambling‐related harms.